Pengaruh Gempabumi Tektonik Terhadap Aktivitas G. Gede - Sri Hidayati; Cecep Sulaeman; Supartoyo Supartoyo; Estu Kriswati (Pusat Survei Geologi, 2018)
In addition to home for seven active volcanoes, West Java, is also having high tectonic activity, owing to its close distance from subduction zone and crustal fault. The Cimandiri Fault extends about 100 km from southwest to the northeast ward through Sukabumi area. Gede Volcano with high seismic activity is sitting 20 km north of Cimandiri Fault. Shallow earthquakes often occur around Gede volcano and their sources are fairly close to the Cimandiri valley. Feltearthquakes occurred in 2007, 2010, 2012 and 2014,where the source supposed to be around Cimandiri valley,were followed by volcano-tectonic (VT) earthquake swarms in Gede Volcano. These swarms probably indicate that there is a linkage between tectonic and Gede volcano activities. However, the swarms were followed by less significant changes in volcanic activity. GPS data during measurement period of 2006-2015 show the existence of a fault with main stress in the northwest-southeast direction. The mechanism of the Cimandiri Fault is reverse fault with sinistral slip component and sinistral strike slip fault, while the swarm of VT earthquakes in Gede Volcano is dominated by reverse and normal faults. Tectonic earthquakes may trigger nearby volcanic eruption; it depends on the state of magma of the volcano and the magnitude of the earthquake.Keyword: Tectonic, Cimandiri fault, VT earthquake, Gede Volcano.